2017
DOI: 10.2147/ott.s148182
|View full text |Cite
|
Sign up to set email alerts
|

Advances in T-cell checkpoint immunotherapy for head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) has been found to be a complex group of malignancies characterized by their profound immunosuppression and high aggressiveness. In most cases of advanced HNSCC, treatment fails to obtain total cancer cure. Efforts are needed to develop new therapeutic approaches to improve HNSCC outcomes. In this light, T-cells “immune checkpoint” has attracted much attention in cancer immunotherapy. It has been broadly accepted that inhibitory T-cell immune checkpoints contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 75 publications
(68 reference statements)
0
16
0
Order By: Relevance
“… 8 Other PD-L1/PD-1 blocking antibodies, including nivolumab, atezolizumab, durvalumab and avelumab, have been approved for clinical use. 9 – 13 In 2017, pembrolizumab was the first FDA-approved immunotherapeutic agent for the treatment of solid tumors with unresectable mismatch-repair deficiency and microsatellite instability. 14 …”
Section: Introductionmentioning
confidence: 99%
“… 8 Other PD-L1/PD-1 blocking antibodies, including nivolumab, atezolizumab, durvalumab and avelumab, have been approved for clinical use. 9 – 13 In 2017, pembrolizumab was the first FDA-approved immunotherapeutic agent for the treatment of solid tumors with unresectable mismatch-repair deficiency and microsatellite instability. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Among these four gene clusters, we are particularly interested in the ones related to B cell receptor signaling pathway or B cell immunity, which have a favorable role in patient survival with HNSCC when expressed higher. Although the critical role of immune activity on cancer development, treatment, and prognosis have been more and more recognized in HNSCC, most of the findings were mainly related to T cell immunity, including its role in immunodeficiency or suppression in cancer development, antitumor therapy, and prognosis of HNSCC 34–38 . Roles of B cells in HNSCC are still not clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 blockade has been shown to prevent the development of carcinogen-induced oral premalignant legions and prevent the malignant transformation [12,13]. While clinical studies of PD-1 blockade exclusively on oral squamous cell carcinoma (OSCC) are not available, study on head and neck squamous cell carcinoma (HNSCC) has shown that a subset of patients benefit from this treatment; leading to the approval of PD-1 blocking antibody for patients with platinum-refractory recurrent and/or metastatic HNSCC [14,15]. These findings, however, further highlight that a majority of the patients do not respond to this therapy.…”
Section: Discussionmentioning
confidence: 99%